Relationship between Employees' Characteristics and Occupational Safety Climate in Phosphoric Acid Industry - Deanida Ankhofiya; Dayinta Annisa Syaiful; Endang Dwiyanti (Universitas Airlangga, 2023)
Introduction: The Indonesian government has issued, through the Ministry of Manpower, an announcement that occupational health and safety is the creation of a conducive employment climate. This research aims to determine the relationship between characteristics of employees (age, education level, and job title or position) and work safety climate in the Phosphoric Acid Industry. Method: This research is an observational study with quantitative method. The population of this research is the employees of the phosphoric acid plant in the Phosphoric Acid Industry, totaling 44 people and total sampling technique as the sampling method. The researchers used the Pearson Spearman correlation test. Result: All dimensions of occupational safety have a weak correlation with the age of employees. Several dimensions have negative correlations with age like dimension of employees' occupational safety priority and unacceptable risks, dimension of employees' occupational safety commitment, dimensions of priority and occupational safety management capability. All dimensions of occupational safety climate have a positive correlation with the level of education. Dimension of trust toward the organization, dimensions of priority, and occupational safety management capability; dimension of occupational safety empowerment have moderate correlations with education level. Most dimensions of occupational safety climate have a negative correlation with the job positions. There is one dimension that is positively correlated with the job position, namely the dimension of trust toward the organization. Conclusion: The results of the study found that there was no strong relationship between employee characteristics (age, education level, position) with the dimensions of work safety climate.